Labor migration: Macroeconomic and demographic outlook for Europe and neighbourhood regions - Vladimir Borgy; Xavier Chojnicki (Center for Social and Economic Research (CASE), 2008)
In this paper, we assess the demographic and economic consequences of migrations in Europe and neighbourhood countries. In order to do so, we rely on a multi-region world overlapping generations model (INGENUE2). The rich modeling framework of this multi-regions model allows us to put into connection migration with the "triangular" relationship between population aging, pension reforms and international capital markets. With this model, we are also able to quantify the demographic and economic consequences of migration ows on both the regions receiving and losing migrants. Our analysis is based on a very detailed migration scenario between Western Europe and the Neighborhood regions constructed by taking into account both the current situation and some prospective empirical scenarios. Our quantitative results shed some light on the long term consequences of migration on regions that are not at the same stage in the ageing process. Concerning the regions receiving migrants, despite some improvement of their public pension system, it appears that our realistic migration scenario does not offset the effect of ageing in these regions, leaving room for pension reforms. Concerning the regions losing migrants, the adverse economic consequences of emigration appear to be all the more important than the region is advanced in the ageing process (and is already suffering from a declining population).
Keywords: F21; C68; J61; H55; F21; C68; J61; H55; 330; CGEM; Migration; International capital flows; Neighbourhood policy; Arbeitsmigranten; Allgemeines Gleichgewicht; Overlapping Generations; Alternde Bevölkerung; Rentenreform; Internationaler Finanzmarkt; Wirkungsanalyse; Westeuropa; Welt